An Approach of the System and Mechanism for Telecoms High-Tech Innovation - Jianjun Bao; Yaoxing Jin (Dianxin kexue)
As high-tech innovation being the foundation of innovation in China, and the initiative of the development of enterprises, according to the characteristics of telecoms, the paper describes the main targets of high-tech innovation, and further explores the system and mechanism issues in telecoms for high-tech innovation,such as divisions and structure organisations,the source of high-tech innovation, R＆amp;D dicision making, the innovation processes, and the applications of the results of innovation, etc.